The Effect of Interpersonal Relationships of Marine Sports Class Participating College Students on School Life Satisfaction - Chun-Ho Yang, Yeong-Gwon Jo, Do-Woong Ham (International Journal of Advanced Science and Technology, 2020)
Background/Objectives: This study was performed to examine the relationship between self-identity and career preparation behavior among college sports players.